"Negro rhythm in the Americas"- being extracts from an article originally written in Spanish - Oderigo, Néstor R. Ortiz (International Library of African Music, 1956)
The drum language was imported to the New World by Negroes. Fernando Ortiz, the great Cuban scholar, in his book entitled ‘Los Negros Esclavos’ (La Habana, 1916) writes “During the conspiratorial days, the Negroes could understand each other by transmitting their rebellious ideas from one zone to another by means of the sound of their drums”. Moreover, in African and Afro-American music, drums are not only rhythmical instruments- Cultural anthropologists and ethnologists have long accepted their melodic character. Twenty five years ago the well-known musicologist, Dr. Erich Moritz von Hornbostel noted the fact that striking upon different parts of the drum head produced different notes and created a certain degree of polyphony. And more recently Dr. Melville Herskovits, in his book entitled “Man and his Works” (Nueva York, 1948) wrote that drums never completely lack tonality.
Keywords: African Music